The effects of slow-release copper boluses on cow reproductive performance and calf growth - Arthington, J.D.; Larson, Robert L.; Corah, L.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two Kansas cow/calf herds known to be copper deficient were utilized to examine the effect of slow-release copper boluses. In herd I, 34 spring-calving cows and calves were divided into a treated and control group at 3-4 months following calving. In herd II, 1106 fall-calving cows and 172 calves were divided into a treated and control group at 3-4 months following calving. In both herds, cow liver and serum samples were collected and assayed for copper and iron. Cows in herd II were also examined for various reproductive parameters. Calf ADG was monitored over a 42-day treatment period in herd I, and a comparison of calf weaning weights was made in herd II. We concluded that copper boluses elevated liver copper levels. However, no effect on reproductive performance was noted, and calf performance was adversely affected.
Keywords: Beef; Copper; Iron; Weight gain; Reproduction